La Tunisie: carrefour du Judaïsme antique et moderne - Allouche, Félix (Evidences, 1949)
Keywords: Judaïsme – Djerba

Insularity (The Palestine Post, 1949)
In a talk about the island of Djerba , a recent speaker on the British broadcasting system marvelled that the main ambition of the natives seemed to be to emigrate, make a fortune out of grocery, and return to die in easeful respectability on their beloved island
Keywords: Judaïsme – Djerba

Les origines et l’habitat des Juifs en Tunisie - Donio, Elie (Bulletin Economique et Social de la Tunisie, 1949)
Keywords: Judaïsme – Djerba